2016
DOI: 10.3906/biy-1503-16
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a transferrin-targeted M13-based gene nanocarrier and evaluation of its efficacy for gene delivery and expression in eukaryote cells

Abstract: Bacteriophages are appropriate gene carriers that might be targeted toward target cells using different strategies. Here we prepared a transferrin-targeted M13-based gene nanocarrier (Tf-targeted M13-GFP) and examined its gene delivery and expression efficacy in the AGS cell line. M13 phagemid particles bearing a GFP expression cassette (M13-GFP) were obtained from a recombinant lambda phage through an in vivo excision procedure. Chemical coupling of human holotransferrin molecules (Tf) to the surface of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The VLPs self-assemble, each containing 360 molecules of the major capsid protein VP1, and can encapsidate heterologous DNA or proteins. MPyV VLPs transduce these cargos into mammalian cells, , and in the case of DNA transfer, ensure long-term gene expression. ,, Similar to the wild-type virus, MPyV VLPs interact with a wide range of cells via sialic acid on the cellular surface; specific targeting thus requires modification of the capsid structure with various ligands, which has been repeatedly achieved by genetic , or chemical means. , Our previous work demonstrated that chemical conjugation of Tf on the VLP surface prevents nonspecific VP1-mediated interaction with sialic acids on the cellular surface and provides efficient targeting to cancer cells that overexpress TfR . The feasibility of using other VLPs for active Tf-TfR targeting has been examined in numerous studies, none of which addressed VLP targeting efficacy in biofluids.…”
Section: Introductionmentioning
confidence: 99%
“…The VLPs self-assemble, each containing 360 molecules of the major capsid protein VP1, and can encapsidate heterologous DNA or proteins. MPyV VLPs transduce these cargos into mammalian cells, , and in the case of DNA transfer, ensure long-term gene expression. ,, Similar to the wild-type virus, MPyV VLPs interact with a wide range of cells via sialic acid on the cellular surface; specific targeting thus requires modification of the capsid structure with various ligands, which has been repeatedly achieved by genetic , or chemical means. , Our previous work demonstrated that chemical conjugation of Tf on the VLP surface prevents nonspecific VP1-mediated interaction with sialic acids on the cellular surface and provides efficient targeting to cancer cells that overexpress TfR . The feasibility of using other VLPs for active Tf-TfR targeting has been examined in numerous studies, none of which addressed VLP targeting efficacy in biofluids.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our results indicate that PVLP can be efficiently retargeted using surface attachment of Tf, expanding the family of VLPs that can operate in a similar way in numerous types of cancer cell lines. These include VLPs based on Brome mosaic virus, adenovirus, and various bacteriophages. ,, The PVLP-Tf * conjugates show notably high uptake, especially to leukemia CCRF-CEM cells (up to 120-fold compared to the control). To the best of our knowledge, comparably high values have not been documented to date for any other cell line and VLP.…”
mentioning
confidence: 99%
“…For example, nonspecific amide-based bioconjugation via lysines on VLP , produces a statistical orientation of protein on the surface and correspondingly low recognition rate by TfR. On the other hand, selective conjugation via a well-defined and properly oriented position can overcome this problem. ,,, For Tf * attachment, we utilized the molecularly defined glycosidation pattern, which can be selectively transformed to a “clickable” moiety (Figure ) and ligated to a VLP using Cu-catalyzed azide–alkyne cycloaddition (click chemistry) . This conjugation approach provides a high degree of flexibility of Tf * attached to a particle and a preferential Tf * orientation for interaction with TfR.…”
mentioning
confidence: 99%